Photo Narratives - Lorena López Cupita (Academia y Virtualidad)
This research aimed to enhance meaningful literacy practices among a group of pre-service English teachers through the use of photo narratives. The researcher conducted a survey with the participants, revealing that their writing skills during high school had become “frozen” due to the COVID-19 pandemic. Additionally, students reported that many writing activities in their schools lacked significance, resulting in their literacy skills being below the expected level for the academic environment. To address this issue, the teacher developed workshops that encouraged students to take photographs related to their personal context, thereby fostering meaningful literacy practices. Data for this pedagogical intervention were collected through students’ written reflections and a follow up survey. The results indicate that through photo narratives, students were able to express their emotions regarding topics of personal interest. Furthermore, these visual narratives helped students gain a better understanding of their context in relation to national history. As a result, they became active learners, exploring and analyzing their surroundings, which are rich in social content. In conclusion, photo narratives can serve as an effective strategy in English as a Foreign Language (EFL) classes to promote meaningful learning among learners.